Human Immunodeficiency Virus and Hepatitis B Virus Co-infection: A Cross-sectional Household Survey in Kiruhura District, Southwestern, Uganda - Apecu, Richard Onyuthi; Bagenda, Fred; Byarugaba, Frederic; Bum, I. I. Yap (International Journal of tropical disease & Health, 2018)
The aim of this study was set to determine the prevalence of HIV/HBV co-infections and the associated risk factors in the general population in the district of Kiruhura-Uganda. A cross-sectional household survey was conducted from April 2014 to November 2014 and 1874 people were recruited on to the study. Blood samples collected from research subjects were analyzed for HI antibodies, HBsAg and HBcAb antibodies. Social-demographic data were captured using a questionnaire. Chi-square tests and bivariate logistic regression were used to determine the association between predictor variables. P-values at 95% confidence interval were considered significant if < 0.05. The overall viral mono infections in the study population for HIV, HBsAg and HBcAb were 6.6% (CI; 5.5-7.8), 4.1% (CI; 3.3-5.1); and 32.8% (CI; 29.7-33.9%) respectively. Meanwhile, the prevalence of current HBV (HIV/HBsAg) and lifelong HBV (HIV/ HBcAb) coinfection was 0.6% and 2.4% respectively in the whole study population with children 5years and below having a prevalence of 0% for both co-infections. Prevalence of both HIV/HBsAg and HIV/HBcAb coinfection was higher among male gender and age group 26-45years. HIV/HBsAg coinfection was associated with being male OR = 5.5 (95% C I: 1.2 – 25.5), p-value= 0.03 and belonging to Bahima tribe OR=3.9, (95%CI: 1.1-13.5), p-value=0.032. HIV/HBcAb co-infection was associated with having high education level OR=2.1 (95% CI: 1.1 - 3.9) p-value = 0.02 and belonging to Banyoro/Batoro tribe OR=6.1, (95%CI: 1.3-28.3), p-value=0.02. Although the prevalence of acute and chronic HBV (HIV/HBV) coinfection among the study population in Kiruhura district Uganda was low, the prevalence is still substantial enough to cause a high burden of morbidity and mortality among the study population.
Keywords: Associated factors; Coinfection; HBcAb; HBsAg; HIV; Prevalence; Uganda